2019
DOI: 10.1145/3285953
|View full text |Cite
|
Sign up to set email alerts
|

Near-optimal Linear Decision Trees for k-SUM and Related Problems

Abstract: We construct near-optimal linear decision trees for a variety of decision problems in combinatorics and discrete geometry. For example, for any constant k, we construct linear decision trees that solve the k-SUM problem on n elements using O (n log 2 n) linear queries. Moreover, the queries we use are comparison queries, which compare the sums of two k-subsets; when viewed as linear queries, comparison queries are 2k-sparse and have only {−1, 0, 1} coefficients. We give similar constructions for sorting sumset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Using folklore meet-inthe-middle algorithms, k-SUM can be solved in time O(n k/2 ) if k is odd, and in time O(n k/2 log n) if k is even. Recently, Kane, Lovett, and Moran [26] showed that it can be solved in time O(n log 2 n) in the linear decision tree model, improving on previous polynomial bounds [13,19].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Using folklore meet-inthe-middle algorithms, k-SUM can be solved in time O(n k/2 ) if k is odd, and in time O(n k/2 log n) if k is even. Recently, Kane, Lovett, and Moran [26] showed that it can be solved in time O(n log 2 n) in the linear decision tree model, improving on previous polynomial bounds [13,19].…”
Section: Introductionmentioning
confidence: 87%
“…Finally, we consider the nonuniform decision tree complexity, also known as query complexity, of the two problems. By applying a recent result of Kane, Lovett, and Moran [26], we can bound the number of algebraic tests that are required to detect copies of P in an input set S. In fact, if the pattern P is a fixed parameter, that is, when P is not part of the input, but known at the algorithm design time, then the decision tree in the statement above only involves linear tests.…”
Section: Corollary 3 There Exists Anmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the x-coordinates of the O(n 2 ) intersections of a set of n lines can be sorted using O(n 2 ) comparisons [58], since these O(n 2 ) values come from O(n) real numbers. (Another example from Fredman's original paper is the well-known X + Y sorting problem, although for the decision tree complexity of that particular problem, simpler [58] and better [45] methods were later found.) We show that this type of result is not limited to the sorting problem alone, and that logarithmic-factor shavings in the decision tree setting are actually not difficult to obtain for many other problems, including point location of multiple query points in multiple subdivisions, assuming that the query points and subdivision vertices originate from O(n) real numbers.…”
Section: Second Approach Via Decision Treesmentioning
confidence: 99%
“…Our model is also related to linear decision tree complexity, see, e.g., [7,14], though such lower bounds typically involve just seeing a threshold applied to Mv i , and typically M is a vector. In our case, we observe the entire output vector Mv i .…”
Section: Introductionmentioning
confidence: 99%